A Study on the Placement Evaluation and Marketing Strategy of Shared Power Banks in Singapore - Wu, Yanxi (International Journal of Global Economics and Management, 2024)
The sharing economy, marked by collaborative consumption, has seen considerable growth globally. While prevalent in China, its popularity lags in other nations. This paper focuses on power bank sharing services in Singapore, a country embracing innovative sharing solutions. With rising mobile device usage, power bank sharing addresses the need for convenient, on-the-go charging. This paper employs a SWOT analysis, and evaluates a specific power bank sharing company in Singapore. Strengths lie in the app's convenience and growing electronic device reliance, while weaknesses encompass privacy and safety concerns. Opportunities arise from the city-state's tech-savvy and Chinese-dominated population and compact urban landscape, which makes them easily accept this new service. However, threats include regulatory uncertainties and single profit mode do need to be considered. In conclusion, Singapore's demographic and sharing-friendly environment positions power bank sharing as a potent manifestation of the sharing economy's innovation, catering to contemporary demands for accessible and sustainable energy solutions.